The Implementasi Sistem Evaluasi Eksternal dan Manajemen Akreditasi dalam Peningkatan Mutu Pendidikan: Studi Kasus di Madrasah Tsanawiyah Al Huda Sukajadi Kecamatan Pamarican Kabupaten Ciamis - Mulyani, Sri; Mulyawan Shafwandy Nugraha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to systematically analyze the literature on the implementation of external evaluation systems and accreditation management in improving the quality of Islamic education. It also seeks to provide a more comprehensive understanding of best practices that can be applied by Islamic educational institutions in responding to increasingly complex quality demands. Using the Systematic Literature Review (SLR) method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, this study identifies themes, strategies, and challenges found in previous studies. Articles were identified from Google Scholar, Garuda, and ScienceDirect databases within the 2012–2024 period. The selection process involved a step-by-step screening of titles and abstracts, resulting in 15 main articles for further in-depth review. The findings indicate that external evaluation functions as a strategic instrument to enhance accountability, transparency, and quality control in educational institutions. Key themes identified include the importance of a Total Quality Management (TQM) culture, the strategic role of Management Information Systems (MIS) in data governance, and the gap between administrative compliance and substantive quality improvement. This study concludes that effective accreditation management requires a shift from a bureaucratic approach toward a culture of continuous improvement integrated with Islamic values and oriented toward overall educational quality enhancement.